Teaching in a Small Rural School During the 1930s: An Oral History - Hemmings, Brian (Australian and International Journal of Rural Education, 1995)
This article reports on a person's recollections of teaching in a single-teacher school during the period 1937 to 1939, These recollections offer a rich and interesting picture of that time and, in addition, allow comparisons to be drawn with present day small school teaching experiences. Recollection or oral history is a method of enquiry that is freely criticised. As documented by Spaull (1988) three common arguments are raised against the oral history procedure: one, it is unrepresentative and thus the reliability of the source can be questioned; two, evidence based on memory reconstructions can be challenged as too subjective; and three, interviewing can lead to inhibitions and distortions from the interviewee. Despite these criticisms, the oral history procedure is currently enjoying a resurgence in educational research and provides a lens to view teaching in a small school during the late 1930s in rural New South Wales (NSW). The interviewee1. was interviewed on three separate occasions from March 1994 till December 1994. Each interview ran for approximately one hour and notes were recorded throughout the interview sessions to allow for later analysis. The analysis was based on a series of coding steps known as open, axial, and selective coding (Neuman, 1991) and revealed six categories: (1) appointment to the far-west area; (2) description of the school setting; (3) teacher responsibilities; (4) characteristics of the student body; (5) curricular organisation; and, (6) departmental inspection. Each category of findings is discussed in the following section.